PENETRASI NEGARA DI DANAU TOBA (Studi Kasus Pengembangan Destinasi Pariwisata di Danau Toba) - Sarmina Purba; Tito Handoko (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
In accordance with the data obtained that mentions that Lake Toba belongs to the KSPN (strategic area of national tourism), it is necessary to take coordinated, systematic, directed and integrated measures so that the need for an action aimed at accelerating development with a policy called state penetration. The purpose of this research is to know what is an obstacle to the development of Lake Toba as a leading tourist destination on a national and international scale and to know the efforts that need to be made, especially the implementing body of the lake toba authority (BPODT) in addressing the problems that become obstacles to Lake Toba as a priority tourist destination. This study uses qualitative approach with descriptive method. The results of research on the penetration of the country in order to accelerate the development of lake toba tourism is a manifestation of the potential seen if Lake Toba can be used as a priority tourism even super priority on an international scale. The obstacles encountered by BPODT are land ownership issues and the community is less participating in accelerating development. The efforts made by the Lake Toba Authority (BPODT) are to improve authoritative and coordinated functions.Keywords : Country Penetration